Current teaching practice for religious education in Hong Kong: implications for 'learning from religion' - Wong, Mei-Yee (Journal of beliefs and values, 2019)
The human development (HD) model for religious education (RE) emphasises how students benefit from studying religion. However, detailed teaching practices for 'learning from religion' are not fully understood. In this article, lesson observations, school documents and interview data were collected from two Christian primary schools in Hong Kong (HK) . Two lessons were analysed as paradigmatic examples of the teaching for student development in RE lessons. This study found that the teachers helped their students engage in religion by giving them opportunities to associate religion with their lives through religious and moral-related contents. The use of daily life and religious experiences with discussions was the pedagogical approach for moving RE from just 'the teaching of religion'. Moreover, various opportunities for student reflections to enhance personal and moral development were observed. Future studies should consider examining the theory of the adopted model and its classroom practice, which can aid understanding regarding the role of RE for student development and its global identity.